Edukasi Konsumsi Sari Kacang Hijau dalam Upaya Pencegahan Anemia pada Ibu Hamil di BPM Muzilatulnisma Kota Jambi - Sirly Patriani; Selpyani Sinulingga (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Anemia is the biggest public health problem in the world, especially among pregnant women. The prevalence of anemia in pregnant women throughout the world is 41.8%. 60% of cases of anemia in pregnant women are due to iron deficiency. The risk of pregnant women who experience anemia faces the risk of death during pregnancy. Every year 500 thousand postpartum maternal deaths occur throughout the world, with 20-40% of the main causes of death being anemia. Anemia occurs due to a lack of iron and folic acid in the body. Women who suffer from anemia during pregnancy have the potential to give birth to babies with low birth weight. The impact of iron deficiency during pregnancy can be risky for the mother and fetus, bleeding occurs and the fetus can cause LBW. To prevent anemia in pregnant women, the pharmacological method is by consuming Fe tablets and the non-pharmacological method is by consuming foods containing iron from animal ingredients and vegetable ingredients such as nuts, tempeh, anemia counseling and screening. One type of legume is green beans. Efforts that can be made to provide knowledge about the use of consuming green bean juice to prevent anemia in pregnant women are by providing education in the form of counseling using leaflets. This community service activity was carried out for pregnant women with a total of 15 pregnant women. The method used is to provide health education by providing counseling using leaflets. The result of the service was an increase in knowledge after being given counseling using leaflets